MODUL PRAKTIKUM JARINGAN EIGRP - Marcus Mulyadharma Weking; Pande Ketut Sudiarta; I Putu Ardana (Jurnal SPEKTRUM, 2021)
Writing a thesis report with the title EIGRP Network Practicum Module aims to increase theknowledge and skills of Udayana University Electrical Engineering students, especially thosewho concentrate on Telecommunication Engineering and Multimedia Networks in managing theEIGRP network and this thesis is also the requirements for graduation from the final level ofundergraduate or S1 lectures. The lack of learning media related to this protocol makes itdifficult for students to understand how the EIGRP dynamic route protocol works. It is importantto learn the EIGRP dynamic route protocol because it is useful in managing building-scalenetwork routes and between buildings. The EIGRP experiments carried out in the practicummodule are divided into several variations with the general purpose of understanding how theEIGRP protocol works, configurations, and variables. This practicum also contains how EIGRPworks using metrics as a benchmark in determining the best possible route along with analyzingmetrics using mathematical equations. The EIGRP network practicum module has been testedon 10 practitioners who are selected students on the condition that these students have studiedand mastered network fundamentals and routing concepts in the Telecommunication NetworkEngineering course. Practical activities in the sequence are working on preliminary reports, pretests,practical module experiments, final reports, questionnaires, and post-tests. In generalterms, this practicum module is deemed capable of increasing the understanding of thepractitioner regarding the EIGRP protocol. The work stages in this practicum module are easyto understand and follow by the practitioner. 7 out of 10 practitioners strongly agree if theEIGRP network practicum module applied to the Telecommunication Network Practicum Course.